Perovskite solar cell and method of manufacturing the same
Patent Information
- Application Number
- CN202611437072.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]本申请的主要目的在于提供一种钙钛矿太阳能电池及其制备方法,以解决现有技术中仅对透明导电氧化物进行P1划线影响对钙钛矿层的结构和性能的问题
[0020]随后通过P2激光划线形成第二激光沟槽,以及P3激光划线形成第三激光沟槽,结合P1激光划线形成的第一激光沟槽,维持标准的子电池片单片串联架构,并基于钙钛矿平面区域的结晶质量提升,使得P1-P2之间的间距,以及P2-P3之间的间距均能够进一步缩小,从而增加单片子电池片的发电面积,提升发电能力。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This application relates to the field of perovskite solar cell technology, and in particular to a perovskite solar cell and its fabrication method. Background Technology
[0002] Perovskite materials have strong light absorption, adjustable band gap, and can be prepared in low-temperature solutions. Over the past decade, their efficiency has rapidly increased to around 27%. They also have the advantages of being lightweight, flexible, and low-cost. However, reliable and scalable methods are still needed to manufacture large-area solar panels and commercialize this emerging photovoltaic technology.
[0003] To achieve the operating voltage required for large-area components, the industry typically employs a monolithic interconnection structure, which divides the entire cell into multiple sub-cells with a width of 4–12 mm through multiple laser scribing processes and then interconnects them in series. In this process, laser scribing is generally defined as three steps: P1, P2, and P3. Specifically, P1: After the transparent conductive oxide (TCO, usually FTO or ITO) is deposited on the substrate and before the charge transport layer (CTL) and perovskite absorber layer are deposited, the TCO is laser-etched to divide the continuous TCO into several mutually insulated strip bottom electrodes; P2: After the "CTL1 / perovskite absorber layer / CTL2" is stacked and before the top electrode is deposited, laser etching is performed to expose one of the TCO strips isolated by P1, forming a series conductive channel between sub-cells; P3: After the top electrode (usually metal or TCO / metal stack) is deposited, the top electrode and the functional layer above it are laser-etched to complete the top-side isolation of adjacent sub-cells. According to the above definition, the mainstream layer sequence in the industry can be summarized as follows: substrate → TCO → P1 (etch TCO) → CTL1 → perovskite absorber layer → CTL2 → P2 (etch to TCO) → top electrode → P3 (isolate top electrode). In this layer sequence, P1 is assumed to be completed before perovskite deposition. Therefore, it is assumed that P1 only acts on the TCO monolayer and does not substantially interfere with the subsequent film formation and crystallization of CTL1 and perovskite.
[0004] Traditional P1 processes are generally considered to "only affect TCO and not subsequent layers," but recent research has clearly demonstrated that defective coatings can occur in the perovskite layer near the laser scribing lines in P1, leading to a significant decrease in module efficiency. This means that P1 is not simply a matter of "applying TCO and calling it a day." The trench morphology is transferred to the perovskite layer throughout the coating-drying-crystallization process. Furthermore, due to "confinement crystallization" differences between the scribe area and the substrate, the perovskite crystal orientation, grain size, and defect density near P1 differ significantly from the unscribed area. Additionally, a ridge of approximately 100 nm (laser recasting protrusion) forms at the P1 edge, increasing roughness and defect density. This phenomenon persists in nip and pin structures, nanosecond and femtosecond lasers, and different perovskite precursor systems, indicating that this is a systemic problem of the traditional P1 process, rather than an occasional issue that can be tuned for a specific parameter.
[0005] Traditional P1 processes sacrifice the film formation and crystallization quality of perovskite near P1. P1 trenches, 100nm ridges (laser recasting protrusions) at the edges, and roughness already exist before perovskite deposition, becoming undesirable interfaces in the perovskite coating-drying-crystallization stage. This leads to restricted crystallization and local defects in the perovskite absorber layer due to mechanisms such as restricted crystallization and capillary perforation. Therefore, it is impossible to fundamentally eliminate the interference of P1 on perovskite crystallization. Summary of the Invention
[0006] The main objective of this application is to provide a perovskite solar cell and its fabrication method, in order to solve the problem that in the prior art, simply scribing P1 lines on transparent conductive oxides affects the structure and performance of the perovskite layer.
[0007] In a first aspect, this application provides a method for fabricating a perovskite solar cell, the method comprising the following steps: A transparent conductive layer, a first charge transport layer, and a perovskite absorption layer are sequentially fabricated on a transparent glass substrate. The perovskite absorption layer, the first charge transport layer, and the transparent conductive layer are scribed with P1 laser to form a first laser groove; A second charge transport layer is prepared on the perovskite absorption layer, the second charge transport layer covering the perovskite absorption layer, and covering the bottom and walls of the first laser trench; The second charge transport layer, the perovskite absorption layer, and the first charge transport layer are scribed with P2 laser to form a second laser groove; A metal electrode layer is fabricated on the second charge transport layer, the metal electrode layer covering the second charge transport layer and the trench walls and bottom of the second laser trench; The metal electrode layer is scribed with P3 laser to form a third laser trench to isolate the metal electrode layer.
[0008] In embodiments of this application, after performing the P1 laser scribing and before preparing the second charge transport layer, the following preparation steps are further included: A passivation layer is prepared on the surface of the perovskite absorber layer.
[0009] In the embodiments of this application, the sequential fabrication of a transparent conductive layer, a first charge transport layer, and a perovskite absorber layer on a transparent glass substrate includes: A transparent conductive layer is prepared on the transparent glass substrate to obtain transparent conductive glass, wherein the transparent conductive layer is fluorine-doped tin oxide; The transparent conductive glass was ultrasonically cleaned for 13-17 minutes each with a cleaning agent, deionized water, acetone and isopropanol, respectively. The cleaned transparent conductive glass is dried with nitrogen gas. The transparent conductive glass, after being dried with nitrogen, is subjected to ultraviolet / ozone oxidation. The tin dioxide colloidal diluent was mixed with deionized water at a volume ratio of 1:4 and then filtered to obtain the first charge transport layer solution. The first charge transport layer solution is spin-coated onto the transparent conductive layer to obtain a semi-wet film of the first charge transport layer, wherein the spin-coating speed is 3900-4100 r / min and the spin-coating time is 28-32 s; The first charge transport layer semi-wet film is annealed to obtain an electron transport layer, wherein the electron transport layer is the first charge transport layer, and the annealing time is 13-17 min and the annealing temperature is 175-185℃. Cesium iodide, methyl iodide, chloromethyl iodide, formamidine iodide, and lead iodide were dissolved in a DMF / NMP mixed solvent and stirred at 60-80℃ for 2-3 hours before being filtered to obtain a perovskite precursor solution. The perovskite precursor solution is coated onto the electron transport layer to obtain a semi-wet perovskite absorption layer film, wherein the gap between the doctor blade and the surface of the electron transport layer is 280-320 μm, and the coating speed is 4-6 mm / s. The perovskite absorber layer semi-wet film is subjected to vacuum treatment, wherein the vacuum degree of the vacuum treatment is 9-11 Pa and the time is 32-38 s; The perovskite absorber layer semi-wet film after vacuum treatment is annealed to obtain the perovskite absorber layer, wherein the annealing time is 13-17 min and the annealing temperature is 145-155℃.
[0010] In embodiments of this application, the preparation of a passivation layer on the surface of the perovskite absorber layer includes: A passivation solution was prepared by dissolving 2-(cyclohex-1-en-1-yl)ethane-1-ammonium iodide (CHEAI) in isopropanol. The passivation solution is spin-coated onto the perovskite absorber layer to obtain a semi-wet passivation solution film, wherein the spin-coating speed is 2900-3100 r / min and the spin-coating time is 28-32 s; The passivation layer is obtained by annealing the semi-wet film of the passivation solution.
[0011] In embodiments of this application, the fabrication of a second charge transport layer on the perovskite absorber layer includes: Spiro-OMeTAD was fully dissolved in chlorobenzene to obtain the first solution; 4-tert-butylpyridine and lithium bis(trifluoromethanesulfonylimide) were dissolved in acetonitrile to obtain a second solution; The second solution was dissolved in the first solution to obtain the Spiro-OMeTAD solution; Spiro-OMeTAD solution was spin-coated onto the passivation layer to obtain a second charge transport layer semi-wet film, wherein the spin-coating speed was 2900-3100 r / min and the spin-coating time was 28-32 s; Annealing the semi-wet film of the second charge transport layer yields a hole transport layer, wherein the hole transport layer is the second charge transport layer.
[0012] In the embodiments of this application, the sequential fabrication of a transparent conductive layer, a first charge transport layer, and a perovskite absorber layer on a transparent glass substrate includes: A transparent conductive layer is prepared on the transparent glass substrate to obtain transparent conductive glass, wherein the transparent conductive layer is indium tin oxide; The transparent conductive glass was ultrasonically cleaned for 13-17 minutes each with a cleaning agent, deionized water, acetone and isopropanol, respectively. The cleaned transparent conductive glass is dried with nitrogen gas. The transparent conductive glass, after being dried with nitrogen, is subjected to ultraviolet / ozone oxidation for 18-22 minutes. A first charge transport layer solution is prepared, wherein the first charge transport layer solution is a MeO-2PACz / NiOx solution; The first charge transport layer solution is spin-coated onto the transparent conductive layer to obtain a semi-wet film of the first charge transport layer. Annealing the semi-wet film of the first charge transport layer yields a hole transport layer, wherein the hole transport layer is the first charge transport layer, and the annealing time is 13-17 min and the annealing temperature is 145-155℃. Cesium iodide, methyl iodide, chloromethyl iodide, formamidine iodide, and lead iodide were dissolved in a DMF / DMSO mixed solvent and stirred at 60-80℃ for 2-3 hours before being filtered to obtain a perovskite precursor solution. The perovskite precursor solution is coated onto the hole transport layer to obtain a semi-wet perovskite absorber layer film. The perovskite absorber layer is obtained by annealing the semi-wet film of the perovskite absorber layer, wherein the annealing time is 28-32 min and the annealing temperature is 115-125℃.
[0013] In embodiments of this application, after preparing the second charge transport layer and before performing the P2 laser scribing, the preparation method further includes: A BCP protective layer is prepared on the second charge transport layer; And / or, the fabrication of the second charge transport layer on the perovskite absorber layer comprises: C is deposited on the perovskite absorber layer 60 An electron transport layer is obtained, wherein the electron transport layer is the second charge transport layer.
[0014] In an embodiment of this application, the metal electrode layer is a silver electrode layer deposited on the second charge transport layer, and the thickness of the metal electrode layer is 95-105 nm.
[0015] In an embodiment of this application, the second charge transport layer completely fills the first laser trench; And / or, before or after the fabrication of the second charge transport layer, the following fabrication steps are also included: Insulating adhesive is filled into the first laser groove.
[0016] Secondly, this application also provides a perovskite solar cell, which is prepared using the perovskite solar cell preparation method described in any of the above claims.
[0017] Thirdly, this application also provides a perovskite solar cell, which includes a transparent glass substrate, a transparent conductive layer, a first charge transport layer, a perovskite absorption layer, a second charge transport layer and a metal electrode layer stacked sequentially. The perovskite solar cell further includes a first laser trench, a second laser trench, and a third laser trench. The plurality of first laser trenches respectively penetrate the perovskite absorption layer, the first charge transport layer, and the transparent conductive layer. The second charge transport layer covers the bottom and the wall of the first laser trench. The plurality of second laser trenches respectively penetrate the second charge transport layer, the perovskite absorption layer, and the first charge transport layer. The metal electrode layer covers the wall and the bottom of the second laser trench. The plurality of third laser trenches respectively penetrate the metal electrode layer.
[0018] In the perovskite solar cell fabrication method of this application, after sequentially fabricating the first charge transport layer and the perovskite absorber layer on a continuous and flat transparent conductive layer, P1 laser scribing is performed. The P1 laser scribing passes sequentially through the perovskite absorber layer, the first charge transport layer, and the transparent conductive layer, achieving isolation of the transparent conductive layer. Compared to the traditional P1 laser scribing method, which involves grooves and laser-recast protrusions at the groove edges, and significantly increased roughness in the groove region affecting the perovskite absorber layer, this method completely eliminates these effects on the first charge transport layer and the perovskite absorber layer. This overcomes the shortcomings of traditional processes by breaking with conventional solutions. Compared to traditional processes, this significantly reduces the grain size difference between the perovskite absorber layer in the P1 laser scribing region and areas far from the P1 scribing region, resulting in a lower open-circuit voltage (V) for each sub-cell. OC The uniformity of fill factor (FF) is improved, the drag on the module-level photoelectric conversion efficiency (PCE) caused by the adjacent area of P1 laser scribing is significantly reduced, the sensitivity to perovskite precursor formulation and coating method is reduced, the process robustness is enhanced, the lateral migration of iodine ions is effectively blocked, the aging rate of the perovskite solar cell is significantly reduced, and the service life of the perovskite solar cell is improved.
[0019] Subsequently, by depositing a second charge transport layer to cover the perovskite absorption layer and the bottom and sidewalls of the first laser trench, the cross-section of the perovskite absorption layer at the wall of the first laser trench is passivated and isolated, thereby forming a continuous coverage on the wall of the first laser trench and passivating the cross-section of the perovskite absorption layer located on the wall of the first laser trench. Thus, by moving the P1 laser scribing backward and covering the first laser trench with the second charge transport layer and passivating the cross-section of the perovskite absorption layer, the lateral migration of iodine ions is effectively blocked, thereby improving the performance of the perovskite absorption layer.
[0020] Subsequently, a second laser trench is formed by laser scribing with P2, and a third laser trench is formed by laser scribing with P3. Combined with the first laser trench formed by laser scribing with P1, the standard single-cell series architecture of the sub-cell is maintained. Based on the improved crystal quality of the perovskite planar region, the spacing between P1-P2 and between P2-P3 can be further reduced, thereby increasing the power generation area of the single sub-cell and improving the power generation capacity.
[0021] In addition, the second laser trench only involves the second charge transport layer and the perovskite absorption layer, unlike the traditional scheme which also involves the first charge transport layer. Therefore, the P2 process window is widened and the defocusing tolerance is greater. After the trench wall of the first laser trench is passivated by the second charge transport layer, its performance in terms of leakage current and insulation resistance is better than that of the traditional P1 laser scribing scheme. Thus, while maintaining the overall framework of P1 / P2 / P3 monolithic interconnection, the geometric fill factor (GFF) is better than that of the traditional process, and it is suitable for traditional fabrication equipment and can be compatible with formal and inverse structures. Attached Figure Description
[0022] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 This is a schematic diagram of the transparent glass substrate and transparent conductive layer of a perovskite solar cell in one embodiment of this application.
[0023] Figure 2 Is Figure 1 This is a schematic diagram of the first charge transport layer fabricated on the transparent conductive layer.
[0024] Figure 3 Is Figure 2 A schematic diagram of the perovskite absorber layer fabricated on the first charge transport layer.
[0025] Figure 4 Is Figure 3 This is a schematic diagram of P1 laser scribing to form the first laser groove on the perovskite absorption layer, the first charge transport layer and the transparent conductive layer.
[0026] Figure 5 Is Figure 4 A schematic diagram of the fabrication of a second charge transport layer on a perovskite absorber layer.
[0027] Figure 6 Is Figure 5 This is a schematic diagram of P2 laser scribing performed on the second charge transport layer, the perovskite absorption layer, and the first charge transport layer to form a second laser groove.
[0028] Figure 7 Is Figure 6 A schematic diagram of the metal electrode layer fabricated on the second charge transport layer.
[0029] Figure 8 Is Figure 7 A schematic diagram showing the P3 laser scribing of the metal electrode layer and part of the second charge transport layer to form a third laser trench.
[0030] Figure 9 This is an electron microscope schematic diagram of the traditional process where, after the transparent conductive layer is prepared, P1 laser scribing is performed on the transparent conductive layer before the first charge transport layer and the perovskite absorption layer are prepared. The film layer shown in the figure is the perovskite absorption layer. The laser groove outline of P1 after P1 laser scribing is performed on only the transparent conductive layer can be clearly seen in the figure.
[0031] Figure 10 for Figure 4 Electron microscope schematic diagram of the corresponding perovskite absorption layer.
[0032] Figure 11 The graphs show the short-circuit current density and open-circuit voltage of Embodiment 1 and Comparative Example 1 of this application.
[0033] Figure 12 The graphs show the short-circuit current density and open-circuit voltage of Embodiment 2 and Comparative Example 2 of this application.
[0034] Figure 13 The graph shows the photoelectric conversion efficiency and aging trend of Example 1 and Comparative Example 1 of this application.
[0035] Figure 14 The graphs show the photoelectric conversion efficiency and aging trend of Embodiment 2 and Comparative Example 2 of this application.
[0036] The above figures include the following reference numerals: A perovskite solar cell 100 comprises a transparent glass substrate 10, a transparent conductive layer 20, a first charge transport layer 30, a perovskite absorber layer 40, a second charge transport layer 50, a metal electrode layer 60, a first laser trench 70, a second laser trench 80, and a third laser trench 90. Detailed Implementation
[0037] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. This application will now be described in detail with reference to the accompanying drawings and embodiments.
[0038] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments according to this application. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0039] Unless otherwise specifically stated, the relative arrangement, numerical expressions, and values of the components and steps described in these embodiments do not limit the scope of this application. It should also be understood that, for ease of description, the dimensions of the various parts shown in the drawings are not drawn to actual scale. Techniques, methods, and devices known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and devices should be considered part of the specification. In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters in the following drawings denote similar items; therefore, once an item is defined in one drawing, it need not be further discussed in subsequent drawings.
[0040] Please see Figure 1-14 As shown, in a first aspect, this application provides a method for fabricating a perovskite solar cell, the method comprising the following steps: A transparent conductive layer 20, a first charge transport layer 30, and a perovskite absorber layer 40 are sequentially prepared on a transparent glass substrate 10.
[0041] In other words, compared to the traditional process where the transparent conductive layer 20 is prepared on the transparent glass substrate 10 and then scribed with a P1 laser before the first charge transport layer 30 is prepared, this application directly prepares the transparent conductive layer 20, the first charge transport layer 30, and the perovskite absorption layer 40 sequentially on the transparent glass substrate 10, thereby forming a series of flat transparent conductive glass, transparent conductive layer 20, first charge transport layer 30, and perovskite absorption layer 40. Therefore, the prepared first charge transport layer 30 and perovskite absorption layer 40 are highly flat, and since the transparent conductive layer 20 has not yet been scribed with a P1 laser, the first charge transport layer 30 and perovskite absorption layer 40 will not be affected by the first laser groove 70 formed by the P1 laser scribing.
[0042] The perovskite absorption layer 40, the first charge transport layer 30 and the transparent conductive layer 20 are scribed with P1 laser to form a first laser groove 70.
[0043] After sequentially fabricating the first charge transport layer 30 and the perovskite absorber layer 40 on a continuously flat transparent conductive layer 20, P1 laser scribing is performed. The P1 laser scribing passes sequentially through the perovskite absorber layer 40, the first charge transport layer 30, and the transparent conductive layer 20, achieving isolation of the transparent conductive layer 20. Compared to the traditional P1 laser scribing method, which creates grooves and laser-recast protrusions at the groove edges, and significantly increases roughness in the groove region, the first charge transport layer 30 and the perovskite absorber layer 40 in this application are completely free from these effects. This overcomes the shortcomings of traditional processes by breaking with conventional methods. Compared to traditional processes, the difference in grain size between the P1 laser scribing area and the perovskite absorber layer 40 far from the P1 scribing area is significantly reduced, resulting in a lower open-circuit voltage (V) for each sub-cell. OC The uniformity of fill factor (FF) is improved, the drag on the module-level photoelectric conversion efficiency (PCE) caused by the adjacent area of P1 laser scribing is significantly reduced, the sensitivity to perovskite precursor formulation and coating method is reduced, the process robustness is enhanced, the lateral migration of iodine ions is effectively blocked, the aging rate of the perovskite solar cell is significantly reduced, and the service life of the perovskite solar cell is improved.
[0044] A second charge transport layer 50 is prepared on the perovskite absorption layer 40. The second charge transport layer 50 covers the perovskite absorption layer 40 and the bottom and walls of the first laser trench 70.
[0045] By depositing a second charge transport layer 50 to cover the perovskite absorption layer 40 and the bottom and sidewalls of the first laser trench 70, the cross-section of the perovskite absorption layer 40 at the sidewall of the first laser trench 70 is passivated and isolated, thereby forming a continuous coverage on the sidewall of the first laser trench 70 and passivating the cross-section of the perovskite absorption layer 40 located on the sidewall of the first laser trench 70. Thus, by moving the P1 laser scribing back and the coverage of the first laser trench 70 by the second charge transport layer 50 and the passivation of the cross-section of the perovskite absorption layer 40, the lateral migration of iodine ions is effectively blocked, and the performance of the perovskite absorption layer 40 is improved.
[0046] The second charge transport layer 50, the perovskite absorption layer 40 and the first charge transport layer 30 are scribed with P2 laser to form a second laser groove 80.
[0047] A metal electrode layer 60 is fabricated on the second charge transport layer 50, the metal electrode layer 60 covering the second charge transport layer 50 and the trench walls and bottom of the second laser trench 80.
[0048] The metal electrode layer 60 is scribed with a P3 laser to form a third laser trench 90 to isolate the metal electrode layer 60.
[0049] The second laser trench 80 is formed by laser scribing P2, and the third laser trench 90 is formed by laser scribing P3. Combined with the first laser trench 70 formed by laser scribing P1, the standard single-cell series architecture of the sub-cell is maintained. Based on the improved crystal quality of the perovskite planar region, the spacing between P1-P2 and between P2-P3 can be further reduced, thereby increasing the power generation area of the single sub-cell and improving the power generation capacity.
[0050] In addition, the second laser trench 80 only involves the second charge transport layer 50 and the perovskite absorber layer 40, unlike the traditional scheme which also involves the first charge transport layer 30. Therefore, the P2 process window is widened, and the defocus tolerance is greater. After the trench wall of the first laser trench 70 is passivated by the second charge transport layer 50, its performance in terms of leakage current and insulation resistance is better than that of the traditional P1 laser scribing scheme. Without changing the overall framework of P1 / P2 / P3 monolithic interconnection, it achieves a geometric fill factor (GFF) that is better than that of the traditional process; improved component-level series resistance, shunt resistance and hysteresis behavior; benefiting from the improved crystal uniformity near P1 and the passivation of the sidewall of the perovskite absorber layer 40, its long-term stability (at 85℃ / DH, based on MPP tracking) is better than that of the traditional P1 laser scribing process.
[0051] P1 laser scribing, P2 laser scribing, and P3 laser scribing can still be performed using mainstream nanosecond and femtosecond lasers (532nm, 355nm, 1064nm, etc.) without replacing the existing production line laser source. The backfilling of the second charge transport layer 50 can be done using existing methods such as spin coating, evaporation, and CBD, resulting in low production line modification costs. Therefore, this process is suitable for traditional preparation equipment and is compatible with both formal and inverse structures.
[0052] In embodiments of this application, after performing the P1 laser scribing and before fabricating the second charge transport layer 50, the following fabrication steps are further included: A passivation layer is prepared on the surface of the perovskite absorber layer 40. By preparing the passivation layer on the surface of the perovskite absorber layer 40, the unsaturated lead sites in the passivation material can be ion-bonded to precisely repair surface defects, thereby eliminating deep-level traps, improving structural stability, extending carrier lifetime, suppressing ion migration, and improving photoelectric conversion efficiency.
[0053] In the embodiments of this application, the passivation layer can form a mixed solution with the second charge transport layer 50, and the mixed solution can be coated onto the perovskite absorption layer 40 in one step, thereby making the preparation of the passivation layer and the preparation of the second charge transport layer 50 in one step. This significantly reduces the cost of using solutions in the process and enables large-area preparation. Therefore, it significantly improves the preparation efficiency, reduces equipment investment, and lowers production costs such as manpower, equipment, and site.
[0054] Example 1 Please see Figure 1 As shown, transparent conductive glass is obtained by preparing the transparent conductive layer 20 on the transparent glass substrate 10. The transparent conductive layer 20 is fluorine-doped tin oxide. After being scribed by P1 laser, the transparent conductive layer 20 will form multiple independent sub-transparent conductive layers, each of which corresponds to a sub-cell.
[0055] The transparent conductive glass is ultrasonically cleaned sequentially with cleaning agent, deionized water, acetone and isopropanol for 13 min or 17 min respectively, as well as any time between 13 and 17 min, such as 14 min, 15 min and 16 min. Through multiple cleaning processes, dirt, watermarks and other undesirable deposits on the surface of the transparent conductive glass can be effectively removed, so that the first charge transport layer 30 prepared subsequently can be tightly bonded to the surface of the transparent conductive layer 20.
[0056] The cleaned transparent conductive glass is dried with nitrogen gas to quickly remove residual solvents and moisture from the surface of the transparent conductive glass after cleaning, avoiding water stains, oxidation or contamination residues, and ensuring the uniformity and film performance of the first charge transport layer 30 and the perovskite absorber layer 40 in subsequent preparation.
[0057] The transparent conductive glass, after being dried with nitrogen, is subjected to ultraviolet / ozone oxidation. Since nitrogen drying cannot decompose hydrocarbon organic compounds, ultraviolet / ozone oxidation of the conductive glass can excite the generated ozone to produce reactive oxygen free radicals, which oxidize the organic matter into carbon dioxide and water, thereby removing the organic matter attached to the surface of the transparent conductive glass. At the same time, a large number of polar groups such as hydroxyl groups can be introduced into the surface of the transparent oxide layer during this process. Therefore, the contact angle of the transparent conductive layer 20 can be significantly reduced, the wettability and uniformity of the first charge transport layer 30 can be enhanced, and the defects such as pinholes, poor adhesion and delamination caused by residual organic matter can be avoided after the preparation of the first charge transport layer 30 or the perovskite absorption layer 40.
[0058] Please see Figure 2As shown, the tin dioxide colloidal diluent was mixed with deionized water at a volume ratio of 1:4 and then filtered to obtain the first charge transport layer 30 solution.
[0059] The solution of the first charge transport layer 30 is spin-coated onto the transparent conductive layer 20 to obtain a semi-wet film of the first charge transport layer 30, wherein the spin-coating speed is 3900-4100 r / min and the spin-coating time is 28-32 s; The spin coating speed can be 3900 r / min or 4100 r / min, or any spin coating speed between 3900 and 4100 r / min, such as 3910 r / min, 3950 r / min, 3980 r / min, 4000 r / min, 4030 r / min, 4060 r / min, 4095 r / min, etc., which will not be listed here.
[0060] The spin coating time can be 28s or 32s, or any time between 28 and 32s, such as 28.5s, 29s, 29.8s, 30s, 30.4s, 31s, 31.5s, 31.9s, etc., which will not be listed here.
[0061] The first charge transport layer 30 semi-wet film is annealed to obtain an electron transport layer, wherein the electron transport layer is the first charge transport layer 30, and the annealing time is 13-17 min and the annealing temperature is 175-185℃.
[0062] The annealing time can be 13 min or 17 min, or any time between 13 and 17, such as 13.2 min, 13.5 min, 13.9 min, 14.6 min, 15 min, 15.8 min, 16 min, 16.5 min, etc., which will not be listed here.
[0063] The annealing temperature can be 175℃ or 185℃, or any temperature between 175℃ and 185℃, such as 176℃, 177℃, 179℃, 180℃, 182℃, 184℃, etc., which will not be listed here.
[0064] Please see Figure 3As shown, cesium iodide, methyl iodide, chloromethyl iodide, formamidine iodide, and lead iodide were dissolved in a DMF / NMP mixed solvent, and stirred at 60-80℃ for 2-3 hours before filtration to obtain a perovskite precursor solution. The volume ratio of DMF to NMP was 6:1, the concentrations of cesium iodide (22.1 mg), methyl iodide (27 mg), chloromethyl iodide (8 mg), formamidine iodide (248.5 mg), and lead iodide (806.8 mg) were as follows: [The DMF / NMP mixed solvent is missing from the original text]. The stirring temperature for 1 mL is 60℃ or 80℃, or any temperature between 60℃ and 80℃, such as 61℃, 64℃, 67℃, 70℃, 73℃, 75℃, 78℃, etc., which will not be listed here; the stirring time can be 2 hours or 3 hours, or any time between 2 and 3 hours, such as 2.1 hours, 2.3 hours, 2.5 hours, 2.7 hours, 2.8 hours, etc., which will not be listed here.
[0065] The perovskite precursor solution is coated onto the electron transport layer to obtain a perovskite absorber layer 40 semi-wet film. The gap between the scraper and the surface of the electron transport layer is 280-320 μm, that is, the gap can be 280 μm or 320 μm, or any gap width between 280-320 μm, such as 285 μm, 294 μm, 300 μm, 305 μm, 310 μm, 316 μm, etc., which will not be listed here. The coating speed is 4-6 mm / s, that is, the coating speed can be 4 mm / s or 6 mm / s, or any value between 4-6 mm / s, such as 4.1 mm / s, 4.5 mm / s, 4.9 mm / s, 5.2 mm / s, 5.6 mm / s, 5.9 mm / s, etc., which will not be listed here.
[0066] The perovskite absorber layer 40 semi-wet film is subjected to vacuum treatment, wherein the vacuum degree of the vacuum treatment is 9-11 Pa and the time is 32-38 s; the vacuum degree can be 9 Pa or 11 Pa, or any vacuum degree between 9-11 Pa, such as 9.2 Pa, 9.5 Pa, 9.7 Pa, 10 Pa, 10.3 Pa, 10.6 Pa, 10.9 Pa, etc., which will not be listed here.
[0067] The perovskite absorber layer 40, after vacuum treatment, is annealed to obtain the perovskite absorber layer 40. The annealing time is 13-17 min and the annealing temperature is 145-155℃.
[0068] The annealing time can be 13 min or 17 min, or any time between 13 and 17, such as 13.2 min, 13.5 min, 13.9 min, 14.6 min, 15 min, 15.8 min, 16 min, 16.5 min, etc., which will not be listed here.
[0069] The annealing temperature can be 145℃ or 155℃, or any temperature between 145℃ and 155℃, such as 146℃, 147℃, 149℃, 150℃, 152℃, 154℃, etc., which will not be listed here.
[0070] Please see Figure 4 As shown, the perovskite absorption layer 40, the first charge transport layer 30 and the transparent conductive layer 20 are scribed with P1 laser to form a first laser groove 70.
[0071] A passivation solution was prepared by dissolving 2-(cyclohex-1-en-1-yl)ethane-1-ammonium iodide (CHEAI) in isopropanol, wherein the amount of 2-(cyclohex-1-en-1-yl)ethane-1-ammonium iodide was 5 mg and the amount of isopropanol was 1 ml.
[0072] The passivation solution is spin-coated onto the perovskite absorber layer 40 to obtain a semi-wet passivation solution film, wherein the spin-coating speed is 2900-3100 r / min and the spin-coating time is 28-32 s.
[0073] The spin coating speed can be 2900 r / min or 3100 r / min, or any spin coating speed between 2900 and 3100 r / min, such as 2910 r / min, 2950 r / min, 2980 r / min, 3000 r / min, 3030 r / min, 3060 r / min, 3095 r / min, etc., which will not be listed here.
[0074] The spin coating time can be 28s or 32s, or any time between 28 and 32s, such as 28.5s, 29s, 29.8s, 30s, 30.4s, 31s, 31.5s, 31.9s, etc., which will not be listed here.
[0075] The passivation layer is obtained by annealing the semi-wet film of the passivation solution.
[0076] Please see Figure 5 As shown, Spiro-OMeTAD was fully dissolved in chlorobenzene to obtain the first solution, wherein Spiro-OMeTAD was 90 mg and chlorobenzene was 1 ml.
[0077] A second solution was obtained by dissolving 4-tert-butylpyridine and lithium trifluoromethanesulfonylimide in acetonitrile, wherein the amount of 4-tert-butylpyridine was 29 μl and the amount of lithium trifluoromethanesulfonylimide was 23 μl.
[0078] The second solution is dissolved in the first solution to obtain the Spiro-OMeTAD solution.
[0079] Spiro-OMeTAD solution was spin-coated onto the passivation layer to obtain a second charge transport layer 50 semi-wet film, wherein the spin-coating speed was 2900-3100 r / min and the spin-coating time was 28-32 s.
[0080] The spin coating speed can be 2900 r / min or 3100 r / min, or any spin coating speed between 2900 and 3100 r / min, such as 2910 r / min, 2950 r / min, 2980 r / min, 3000 r / min, 3030 r / min, 3060 r / min, 3095 r / min, etc., which will not be listed here.
[0081] The spin coating time can be 28s or 32s, or any time between 28 and 32s, such as 28.5s, 29s, 29.8s, 30s, 30.4s, 31s, 31.5s, 31.9s, etc., which will not be listed here.
[0082] Annealing the semi-wet film of the second charge transport layer 50 yields a hole transport layer, wherein the hole transport layer is the second charge transport layer 50.
[0083] Please see Figure 6 As shown, the second charge transport layer 50, the perovskite absorption layer 40 and the first charge transport layer 30 are scribed with P2 laser to form a second laser groove 80.
[0084] Please see Figure 7 As shown, a metal electrode layer 60 is fabricated on the second charge transport layer 50, and the metal electrode layer 60 covers the second charge transport layer 50 and the trench walls and bottom of the second laser trench 80.
[0085] Please see Figure 8 As shown, the metal electrode layer 60 is scribed with a P3 laser to form a third laser trench 90 to isolate the metal electrode layer 60.
[0086] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 performs the P1 laser scribing step before the preparation of the first charge transport layer 30 and after the preparation of the transparent oxide layer.
[0087] Example 2 Please see Figure 1 As shown, transparent conductive glass is obtained by preparing the transparent conductive layer 20 on the transparent glass substrate 10, wherein the transparent conductive layer 20 is indium tin oxide.
[0088] The transparent conductive glass is ultrasonically cleaned sequentially with cleaning agent, deionized water, acetone and isopropanol for 13 min or 17 min respectively, as well as any time between 13 and 17 min, such as 14 min, 15 min and 16 min. Through multiple cleaning processes, dirt, watermarks and other undesirable deposits on the surface of the transparent conductive glass can be effectively removed, so that the first charge transport layer 30 prepared subsequently can be tightly bonded to the surface of the transparent conductive layer 20.
[0089] The cleaned transparent conductive glass is dried with nitrogen gas to quickly remove residual solvents and moisture from the surface of the transparent conductive glass after cleaning, avoiding water stains, oxidation or contamination residues, and ensuring the uniformity and film performance of the first charge transport layer 30 and the perovskite absorber layer 40 in subsequent preparation.
[0090] The transparent conductive glass, after being dried with nitrogen, is subjected to ultraviolet / ozone oxidation for 18 or 22 minutes, or any time between 18 and 22 minutes, such as 19 minutes, 19.8 minutes, or 21 minutes. Since nitrogen drying cannot decompose hydrocarbon organic compounds, ultraviolet / ozone oxidation of the conductive glass can excite the generated ozone to produce reactive oxygen free radicals, which oxidize the organic matter into carbon dioxide and water, thereby removing the organic matter attached to the surface of the transparent conductive glass. At the same time, a large number of polar groups such as hydroxyl groups can be introduced into the surface of the transparent oxide layer during this process. Therefore, the contact angle of the transparent conductive layer 20 can be significantly reduced, the wettability and uniformity of the first charge transport layer 30 can be enhanced, and the organic matter residue can be avoided, which may lead to pinholes, poor adhesion, and delamination in the first charge transport layer 30 or the perovskite absorption layer 40 after preparation.
[0091] Please see Figure 2 As shown, a first charge transport layer 30 solution is prepared, and the first charge transport layer 30 solution is a MeO-2PACz / NiOx solution.
[0092] The solution of the first charge transport layer 30 is spin-coated onto the transparent conductive layer 20 to obtain a semi-wet film of the first charge transport layer 30.
[0093] Annealing the semi-wet film of the first charge transport layer 30 yields a hole transport layer, wherein the hole transport layer is the first charge transport layer 30, and the annealing time is 13-17 min and the annealing temperature is 145-155℃.
[0094] The annealing time can be 13 min or 17 min, or any time between 13 and 17, such as 13.2 min, 13.5 min, 13.9 min, 14.6 min, 15 min, 15.8 min, 16 min, 16.5 min, etc., which will not be listed here.
[0095] The annealing temperature can be 145℃ or 155℃, or any temperature between 145℃ and 155℃, such as 146℃, 147℃, 149℃, 150℃, 152℃, 154℃, etc., which will not be listed here.
[0096] Please see Figure 3 As shown, cesium iodide, methyl iodide, chloromethyl iodide, formamidine iodide, and lead iodide were dissolved in a DMF / DMSO mixed solvent, and stirred at 60-80℃ for 2-3 hours before filtration to obtain a perovskite precursor solution. The volume ratio of DMF to DMSO was 4:1, with cesium iodide at 19.5 mg, methyl iodide at 23.8 mg, chloromethyl iodide at 12.7 mg, formamidine iodide at 219.3 mg, and lead iodide at 760.7 mg. The DMF / DMSO mixture... The solvent is 1 mL; the stirring temperature is 60℃ or 80℃, or any temperature between 60-80℃, such as 61℃, 64℃, 67℃, 70℃, 73℃, 75℃, 78℃, etc., which will not be listed here; the stirring time can be 2 hours or 3 hours, or any time between 2-3 hours, such as 2.1 hours, 2.3 hours, 2.5 hours, 2.7 hours, 2.8 hours, etc., which will not be listed here.
[0097] The perovskite precursor solution is coated onto the hole transport layer to obtain a perovskite absorber layer 40 semi-wet film.
[0098] The perovskite absorber layer 40 is obtained by annealing the semi-wet film of the perovskite absorber layer 40, wherein the annealing time is 28-32 min and the annealing temperature is 115-125℃.
[0099] The annealing time can be 28 min or 32 min, or any time between 28 and 32 min, such as 28.2 min, 28.5 min, 28.9 min, 29.6 min, 30 min, 30.8 min, 31 min, 31.5 min, etc., which will not be listed here.
[0100] The annealing temperature can be 115℃ or 125℃, or any temperature between 115℃ and 125℃, such as 116℃, 117℃, 119℃, 120℃, 122℃, 124℃, etc., which will not be listed here.
[0101] Please see Figure 4 As shown, the perovskite absorption layer 40, the first charge transport layer 30 and the transparent conductive layer 20 are scribed with P1 laser to form a first laser groove 70.
[0102] A BCP protective layer is prepared on the second charge transport layer 50. The BCP protective layer is prepared on the second charge transport layer 50 by thermal evaporation. The thickness of the BCP protective layer is between 5nm and 10nm. That is to say, the thickness of the BCP protective layer can be 5nm or 10nm, or any value between 5nm and 10nm, such as 6nm, 7nm, 7.5nm, 9nm, etc., which will not be listed here.
[0103] Please see Figure 5 As shown, C is deposited on the perovskite absorber layer 40. 60 An electron transport layer is obtained, wherein the electron transport layer is the second charge transport layer 50. 60 The prepared electron transport layer is the best performing electron transport layer material in inverted perovskite solar cells. It has the ability to quickly capture and vertically transport photogenerated electrons, while also improving short-circuit current, filling grain boundary defects on the perovskite surface, suppressing nonradiative recombination, increasing open-circuit voltage (Voc), and exhibiting strong hydrophobicity and resistance to water penetration.
[0104] Please see Figure 6 As shown, the second charge transport layer 50, the perovskite absorption layer 40 and the first charge transport layer 30 are scribed with P2 laser to form a second laser groove 80.
[0105] Please see Figure 7 As shown in the embodiments of this application, the metal electrode layer 60 is a silver electrode layer deposited on the second charge transport layer 50. The thickness of the metal electrode layer 60 is 95-105nm, that is, the thickness of the metal electrode layer 60 can be 95nm or 105nm, or any value between 95nm and 105nm, such as 97nm, 99nm, 101nm, 103nm, 104nm, etc., which will not be listed here.
[0106] Please see Figure 8 As shown, the metal electrode layer 60 is scribed with a P3 laser to form a third laser trench 90 to isolate the metal electrode layer 60.
[0107] In the embodiments of this application, the second charge transport layer 50 completely fills the first laser trench 70, thereby achieving complete filling of the first laser trench 70 by utilizing the second charge transport layer 50, avoiding additional process steps to fill the first laser trench 70. At the same time, the second charge transport layer 50 is cleverly used to completely fill the first laser trench 70, effectively blocking the perovskite absorption layer 40 within the sidewall of the first laser trench 70, preventing iodine ions from migrating laterally, and improving the performance of the perovskite absorption layer 40.
[0108] In embodiments of this application, the following fabrication steps are further included before or after the fabrication of the second charge transport layer 50: By filling the first laser trench 70 with insulating adhesive, the perovskite absorption layer 40 located on the sidewall of the first laser trench 70 can also be effectively blocked and insulated.
[0109] In some embodiments, after the second charge transport layer 50 is prepared, if the second charge transport layer 50 fills the first laser trench 70, it is not necessary to fill the first laser trench 70 with the insulating adhesive.
[0110] In some embodiments, when the prepared second charge transport layer 50 does not completely fill the first laser trench 70, continuing to fill the first laser trench 70 with the insulating adhesive can effectively block and insulate the perovskite absorption layer 40 located on the sidewall of the first laser trench 70, and can ensure that the prepared metal electrode layer 60 is flatter.
[0111] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that Comparative Example 2 performs the P1 laser scribing step before the preparation of the first charge transport layer 30 and after the preparation of the transparent oxide layer.
[0112] Please see Figure 1-14 As shown, in a second aspect, this application also provides a perovskite solar cell 100, which is prepared using the perovskite solar cell preparation method described in any of the above claims. Therefore, the perovskite solar cell 100 possesses all the aforementioned beneficial effects, which will not be elaborated further here.
[0113] Please see Figure 1-14 As shown, in a third aspect, this application also provides a perovskite solar cell 100, which includes a transparent glass substrate 10, a transparent conductive layer 20, a first charge transport layer 30, a perovskite absorption layer 40, a second charge transport layer 50 and a metal electrode layer 60 stacked sequentially.
[0114] The perovskite solar cell 100 further includes a first laser trench 70, a second laser trench 80, and a third laser trench 90. A plurality of first laser trenches 70 penetrate the perovskite absorption layer 40, the first charge transport layer 30, and the transparent conductive layer 20, respectively. A second charge transport layer 50 covers the bottom and walls of the first laser trenches 70. A plurality of second laser trenches 80 penetrate the second charge transport layer 50, the perovskite absorption layer 40, and the first charge transport layer 30, respectively. A metal electrode layer 60 covers the walls and bottom of the second laser trenches 80. A plurality of third laser trenches 90 penetrate the metal electrode layer 60, respectively.
[0115] Compared to the traditional process where the transparent conductive layer 20 is prepared on the transparent glass substrate 10 and then scribed with a P1 laser before the first charge transport layer 30 is prepared, this application directly prepares the transparent conductive layer 20, the first charge transport layer 30, and the perovskite absorption layer 40 sequentially on the transparent glass substrate 10, thereby forming a series of flat transparent conductive glass, transparent conductive layer 20, first charge transport layer 30, and perovskite absorption layer 40. Therefore, the prepared first charge transport layer 30 and perovskite absorption layer 40 are highly flat, and since the transparent conductive layer 20 has not yet been scribed with a P1 laser, the first charge transport layer 30 and perovskite absorption layer 40 will not be affected by the first laser groove 70 formed by the P1 laser scribing.
[0116] After sequentially fabricating the first charge transport layer 30 and the perovskite absorber layer 40 on a continuously flat transparent conductive layer 20, P1 laser scribing is performed. The P1 laser scribing passes sequentially through the perovskite absorber layer 40, the first charge transport layer 30, and the transparent conductive layer 20, achieving isolation of the transparent conductive layer 20. Compared to the traditional P1 laser scribing method, which creates grooves and laser-recast protrusions at the groove edges, and significantly increases roughness in the groove region, the first charge transport layer 30 and the perovskite absorber layer 40 in this application are completely free from these effects. This overcomes the shortcomings of traditional processes by breaking with conventional methods. Compared to traditional processes, the difference in grain size between the P1 laser scribing area and the perovskite absorber layer 40 far from the P1 scribing area is significantly reduced, resulting in a lower open-circuit voltage (V) for each sub-cell. OCThe uniformity of fill factor (FF) is improved, the drag on the module-level photoelectric conversion efficiency (PCE) caused by the adjacent area of P1 laser scribing is significantly reduced, the sensitivity to perovskite precursor formulation and coating method is reduced, the process robustness is enhanced, the lateral migration of iodine ions is effectively blocked, the aging rate of the perovskite solar cell is significantly reduced, and the service life of the perovskite solar cell is improved.
[0117] By depositing a second charge transport layer 50 to cover the perovskite absorption layer 40 and the bottom and sidewalls of the first laser trench 70, the cross-section of the perovskite absorption layer 40 at the sidewall of the first laser trench 70 is passivated and isolated, thereby forming a continuous coverage on the sidewall of the first laser trench 70 and passivating the cross-section of the perovskite absorption layer 40 located on the sidewall of the first laser trench 70. Thus, by moving the P1 laser scribing back and the coverage of the first laser trench 70 by the second charge transport layer 50 and the passivation of the cross-section of the perovskite absorption layer 40, the lateral migration of iodine ions is effectively blocked, and the performance of the perovskite absorption layer 40 is improved.
[0118] The second laser trench 80 is formed by laser scribing P2, and the third laser trench 90 is formed by laser scribing P3. Combined with the first laser trench 70 formed by laser scribing P1, the standard single-cell series architecture of the sub-cell is maintained. Based on the improved crystal quality of the perovskite planar region, the spacing between P1-P2 and between P2-P3 can be further reduced, thereby increasing the power generation area of the single sub-cell and improving the power generation capacity.
[0119] In addition, the second laser trench 80 only involves the second charge transport layer 50 and the perovskite absorber layer 40, unlike the traditional scheme which also involves the first charge transport layer 30. Therefore, the P2 process window is widened, and the defocus tolerance is greater. After the trench wall of the first laser trench 70 is passivated by the second charge transport layer 50, its performance in terms of leakage current and insulation resistance is better than that of the traditional P1 laser scribing scheme. Without changing the overall framework of P1 / P2 / P3 monolithic interconnection, it achieves a geometric fill factor (GFF) that is better than that of the traditional process; improved component-level series resistance, shunt resistance and hysteresis behavior; benefiting from the improved crystal uniformity near P1 and the passivation of the sidewall of the perovskite absorber layer 40, its long-term stability (at 85℃ / DH, based on MPP tracking) is better than that of the traditional P1 laser scribing process.
[0120] For ease of description, spatial relative terms such as "above," "on top of," "on the upper surface of," "above," etc., are used herein to describe the spatial positional relationship of a device or feature as shown in the figures to other devices or features. It should be understood that spatial relative terms are intended to encompass different orientations in use or operation beyond the orientation of the device as described in the figures. For example, if the device in the figures were inverted, a device described as "above" or "on top of" other devices or structures would subsequently be positioned as "below" or "under" other devices or structures. Thus, the exemplary term "above" can include both "above" and "below." The device may also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatial relative descriptions used herein will be interpreted accordingly.
[0121] Furthermore, it should be noted that the use of terms such as "first" and "second" to define components is merely for the purpose of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be construed as limiting the scope of protection of this application.
[0122] The above are merely preferred embodiments of this application and are not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for preparing a perovskite solar cell, characterized in that, The preparation steps include the following: A transparent conductive layer, a first charge transport layer, and a perovskite absorption layer are sequentially fabricated on a transparent glass substrate. The perovskite absorption layer, the first charge transport layer, and the transparent conductive layer are scribed with P1 laser to form a first laser groove; A second charge transport layer is prepared on the perovskite absorption layer, the second charge transport layer covering the perovskite absorption layer, and covering the bottom and walls of the first laser trench; The second charge transport layer, the perovskite absorption layer, and the first charge transport layer are scribed with P2 laser to form a second laser groove; A metal electrode layer is fabricated on the second charge transport layer, the metal electrode layer covering the second charge transport layer and the trench walls and bottom of the second laser trench; The metal electrode layer is scribed with P3 laser to form a third laser trench to isolate the metal electrode layer.
2. The method for preparing a perovskite solar cell according to claim 1, characterized in that, After performing the P1 laser scribing and before fabricating the second charge transport layer, the following fabrication steps are also included: A passivation layer is prepared on the surface of the perovskite absorber layer.
3. The method for preparing a perovskite solar cell according to claim 1 or 2, characterized in that, The step of sequentially fabricating a transparent conductive layer, a first charge transport layer, and a perovskite absorber layer on a transparent glass substrate includes: A transparent conductive layer is prepared on the transparent glass substrate to obtain transparent conductive glass, wherein the transparent conductive layer is fluorine-doped tin oxide; The transparent conductive glass was ultrasonically cleaned for 13-17 minutes each with a cleaning agent, deionized water, acetone and isopropanol, respectively. The cleaned transparent conductive glass is dried with nitrogen gas. The transparent conductive glass, after being dried with nitrogen, is subjected to ultraviolet / ozone oxidation. The tin dioxide colloidal diluent was mixed with deionized water at a volume ratio of 1:4 and then filtered to obtain the first charge transport layer solution. The first charge transport layer solution is spin-coated onto the transparent conductive layer to obtain a semi-wet film of the first charge transport layer, wherein the spin-coating speed is 3900-4100 r / min and the spin-coating time is 28-32 s; The first charge transport layer semi-wet film is annealed to obtain an electron transport layer, wherein the electron transport layer is the first charge transport layer, and the annealing time is 13-17 min and the annealing temperature is 175-185℃. Cesium iodide, methyl iodide, chloromethyl iodide, formamidine iodide, and lead iodide were dissolved in a DMF / NMP mixed solvent and stirred at 60-80℃ for 2-3 hours before being filtered to obtain a perovskite precursor solution. The perovskite precursor solution is coated onto the electron transport layer to obtain a semi-wet perovskite absorption layer film, wherein the gap between the doctor blade and the surface of the electron transport layer is 280-320 μm, and the coating speed is 4-6 mm / s. The perovskite absorber layer semi-wet film is subjected to vacuum treatment, wherein the vacuum degree of the vacuum treatment is 9-11 Pa and the time is 32-38 s; The perovskite absorber layer semi-wet film after vacuum treatment is annealed to obtain the perovskite absorber layer, wherein the annealing time is 13-17 min and the annealing temperature is 145-155℃.
4. The method for preparing a perovskite solar cell according to claim 2, characterized in that, The preparation of the passivation layer on the surface of the perovskite absorber layer includes: A passivation solution was prepared by dissolving 2-(cyclohex-1-en-1-yl)ethane-1-ammonium iodide (CHEAI) in isopropanol. The passivation solution is spin-coated onto the perovskite absorber layer to obtain a semi-wet passivation solution film, wherein the spin-coating speed is 2900-3100 r / min and the spin-coating time is 28-32 s; The passivation layer is obtained by annealing the semi-wet film of the passivation solution.
5. The method for preparing a perovskite solar cell according to claim 2, characterized in that, The process of fabricating a second charge transport layer on the perovskite absorber layer includes: Spiro-OMeTAD was fully dissolved in chlorobenzene to obtain the first solution; A second solution was obtained by dissolving 4-tert-butylpyridine and lithium bis(trifluoromethanesulfonylimide) in acetonitrile. The second solution was dissolved in the first solution to obtain the Spiro-OMeTAD solution; Spiro-OMeTAD solution was spin-coated onto the passivation layer to obtain a second charge transport layer semi-wet film, wherein the spin-coating speed was 2900-3100 r / min and the spin-coating time was 28-32 s; Annealing the semi-wet film of the second charge transport layer yields a hole transport layer, wherein the hole transport layer is the second charge transport layer.
6. The method for preparing a perovskite solar cell according to claim 1, characterized in that, The step of sequentially fabricating a transparent conductive layer, a first charge transport layer, and a perovskite absorber layer on a transparent glass substrate includes: A transparent conductive layer is prepared on the transparent glass substrate to obtain transparent conductive glass, wherein the transparent conductive layer is indium tin oxide; The transparent conductive glass was ultrasonically cleaned for 13-17 minutes each with a cleaning agent, deionized water, acetone and isopropanol, respectively. The cleaned transparent conductive glass is dried with nitrogen gas. The transparent conductive glass, after being dried with nitrogen, is subjected to ultraviolet / ozone oxidation for 18-22 minutes. A first charge transport layer solution is prepared, wherein the first charge transport layer solution is a MeO-2PACz / NiOx solution; The first charge transport layer solution is spin-coated onto the transparent conductive layer to obtain a semi-wet film of the first charge transport layer. Annealing the semi-wet film of the first charge transport layer yields a hole transport layer, wherein the hole transport layer is the first charge transport layer, and the annealing time is 13-17 min and the annealing temperature is 145-155℃. Cesium iodide, methyl iodide, chloromethyl iodide, formamidine iodide, and lead iodide were dissolved in a DMF / DMSO mixed solvent and stirred at 60-80℃ for 2-3 hours before being filtered to obtain a perovskite precursor solution. The perovskite precursor solution is coated onto the hole transport layer to obtain a semi-wet perovskite absorber layer film. The perovskite absorber layer is obtained by annealing the semi-wet film of the perovskite absorber layer, wherein the annealing time is 28-32 min and the annealing temperature is 115-125℃.
7. The method for preparing a perovskite solar cell according to claim 1 or 6, characterized in that, After fabricating the second charge transport layer and before performing the P2 laser scribing, the fabrication method further includes: A BCP protective layer is prepared on the second charge transport layer; And / or, the fabrication of the second charge transport layer on the perovskite absorber layer comprises: C is deposited on the perovskite absorber layer 60 An electron transport layer is obtained, wherein the electron transport layer is the second charge transport layer.
8. The method for fabricating a perovskite solar cell according to claim 1, 2, 4, or 6, characterized in that, The metal electrode layer is a silver electrode layer deposited on the second charge transport layer, and the thickness of the metal electrode layer is 95-105 nm.
9. The method for preparing a perovskite solar cell according to claim 1, characterized in that, The second charge transport layer completely fills the first laser trench; And / or, before or after the fabrication of the second charge transport layer, the following fabrication steps are also included: Insulating adhesive is filled into the first laser groove.
10. A perovskite solar cell, characterized in that, The perovskite solar cell was prepared using the method described in any one of claims 1-9.
11. A perovskite solar cell, characterized in that, It includes a transparent glass substrate, a transparent conductive layer, a first charge transport layer, a perovskite absorption layer, a second charge transport layer, and a metal electrode layer stacked sequentially. The perovskite solar cell further includes a first laser trench, a second laser trench, and a third laser trench. The plurality of first laser trenches respectively penetrate the perovskite absorption layer, the first charge transport layer, and the transparent conductive layer. The second charge transport layer covers the bottom and the wall of the first laser trench. The plurality of second laser trenches respectively penetrate the second charge transport layer, the perovskite absorption layer, and the first charge transport layer. The metal electrode layer covers the wall and the bottom of the second laser trench. The plurality of third laser trenches respectively penetrate the metal electrode layer.